Influence of biodegradable polymer membrane on new bone formation and biodegradation of biphasic bone substitutes: an animal mandibular defect model study - Jeong-Kui Ku; Young-Kyun Kim; Pil-Young Yun (SpringerOpen, 2020)
Abstract Purpose The purpose of this study was to evaluate the influence of biodegradable polycaprolactone membrane on new bone formation and the biodegradation of biphasic alloplastic bone substitutes using animal models. Materials and methods In this study, bony defect was formed at the canine mandible of 8 mm in diameter, and the defects were filled with Osteon II. The experimental groups were covered with Osteoguide as barrier membrane, and the control groups were closed without membrane coverage. The proportion of new bone and residual bone graft material was measured histologically and histomorphometrically at postoperative 4 and 8 weeks. Results At 4 weeks, the new bone proportion was similar between the groups. The proportion of remaining graft volume was 27.58 ± 6.26 and 20.01 ± 4.68% on control and experimental groups, respectively (P < 0.05). There was no significant difference between the two groups in new bone formation and the amount of residual bone graft material at 8 weeks. Conclusion The biopolymer membrane contributes to early biodegradation of biphasic bone substitutes in the jaw defect but it does not affect the bone formation capacity of the bone graft.